2015
DOI: 10.1002/pola.27905
|View full text |Cite
|
Sign up to set email alerts
|

Highly active polymeric organocatalyst: Chiral ionic polymers prepared from 10,11‐didehydrogenated cinchonidinium salt

Abstract: Since few examples of 10,11-didehydrogenated (3ethynyl) cinchona alkaloids have been utilized as organocatalysts in asymmetric reaction, we synthesized 10,11-didehydrogenated cinchonidine. The 3-vinyl group of cinchonidine was transformed into a 3-ethynyl functionality. Based on the resulting 10,11-didehydrogenated cinchonidine, the corresponding quaternary ammonium salt and its dimers were prepared. The ion-exchange reaction between the quaternary ammonium salt and sodium sulfonate produced the quaternary amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Main chain supported chiral salts immobilised by completely ionic interaction, combining both ionic and covalent bonds or just solely based on covalent immobilisation have been successfully obtained. [366][367][368][369][370] A wide range of structural building blocks have been evaluated in order to optimise the supported catalyst. In most of the cases, it has been possible to adjust the polymer structure to obtain catalysts (286)(287)(288)(289) which are often more selective than the homogeneous analogues.…”
Section: Selectivitymentioning
confidence: 99%
“…Main chain supported chiral salts immobilised by completely ionic interaction, combining both ionic and covalent bonds or just solely based on covalent immobilisation have been successfully obtained. [366][367][368][369][370] A wide range of structural building blocks have been evaluated in order to optimise the supported catalyst. In most of the cases, it has been possible to adjust the polymer structure to obtain catalysts (286)(287)(288)(289) which are often more selective than the homogeneous analogues.…”
Section: Selectivitymentioning
confidence: 99%
“…Throughout the investigation of different phase-transfer catalytic systems, we found that 13 was effective in a three-phase Michael addition of diethyl acetamidomalonate (24) to nitrostyrene (23) (46% ee, Scheme 7). Thus, the native crown ethers (1-3) and the immobilized catalysts (13)(14)(15)(16) were evaluated in this Michael addition (Tables 1 and 2). The results of the reactions with macrocycles 1-3 showed that a higher concentration of the substrate (0.33 M instead of 0.1 M) was favorable.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, numerous methodologies have been developed for the attachment of organocatalysts (e.g., proline, squaramide or thiourea derivatives) to various solid supports, including silica, polystyrene resin, or nanoparticles [7]. On the field of phase-transfer catalysis, several research groups bound cinchona alkaloid-based quaternary ammonium salts to polymers (e.g., to polystyrene or polyethylene glycol) [8][9][10][11][12][13][14][15][16]. In the case of the first derivatives, the alkaloid unit was directly connected to the polymer framework, while in the case of the second-generation catalysts it was recognized that if a spacer is used between the polymer and the active center of the catalyst, the selectivity can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…For the immobilization of method, we developed an ionic immobilization method for chiral organocatalysts, such as MacMillan catalyst and cinchonidinium, via neutralization reaction or ion-exchange reaction with sulfonated polymers [39,40]. The ionic immobilization methodology has been applied for the synthesis of the main chain of chiral polymers, many of which were prepared by intermolecular reactions of chiral organocatalyst dimers with disulfonic acid derivatives [41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%